Frequency-hopping mechanism and control method for nonlinear parity-time-symmetric wireless power transfer systems - Li, Changsheng; Dong, Wenjie; Ma, Haoran; Zhu, Chuanjun (Frontiers in Energy Research, 2023)
Nonlinear parity-time-symmetric wireless power transfer (NPTS-WPT) is a novel wireless power transfer (WPT) technology. NPTS-WPT systems exhibit the resonant frequency bifurcation phenomenon in the strong coupling region. However, working frequency selection mechanisms and control methods for use in the bifurcation region remain unclear. In this study, the description function method was used to model and analyze the dynamics of NPTS-WPT systems. The frequency stability, evolution and convergence characteristics of resonant frequency bifurcation were studied for varying distances between the receiver (Rx) and transmitter circuits varies. In addition, the loop detuning characteristics and the mechanism by which the amplification factor of the operational amplifier influences the system’s frequency-hopping behavior were determined. The detuning rate must be greater than the detuning tolerance to cause resonant frequency-hopping. Moreover, we propose a method to induce changes in the natural frequency of the Rx circuit by adding a detuning control circuit at the Rx, thereby allowing the resonant frequency to be selected and controlled. Finally, the conclusions from the theoretical analysis and the feasibility of the proposed frequency control methods were validated using an experimental system. The proposed resonant frequency control methods offer a viable method for directional frequency selection and artificial frequency control in NPTS-WPT systems operating in the strong coupling region.